2022
DOI: 10.1152/ajpendo.00100.2022
|View full text |Cite
|
Sign up to set email alerts
|

Female and male C57BL/6J offspring exposed to maternal obesogenic diet develop altered hypothalamic energy metabolism in adulthood

Abstract: Maternal obesity is exceedingly common and strongly linked to offspring obesity and metabolic disease. Hypothalamic function is critical to obesity development. Hypothalamic mechanisms causing obesity following exposure to maternal obesity have not been elucidated. Therefore, we studied a cohort of C57Bl/6J dams, treated with a control or high-fat-high-sugar diet, and their adult offspring to explore potential hypothalamic mechanisms to explain the link between maternal and offspring obesity. Dams treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 100 publications
1
17
0
Order By: Relevance
“…We observed that adult male offspring from obese mothers had higher body weight and food intake than offspring from CON mothers, confirming that maternal obesity can increase the risk of obesity in offspring, at least in males. This sex-specific response has been observed in some, 22,23 but not all, 24,25 previous rodent model studies investigating the transgenerational impact of maternal obesity. Previous work in rodent models suggests this hyperphagic/ obesogenic response may be mediated, at least partially, by altered expression of central appetite reward systems including preferential enhancement of orexigenic (NPY/AgRP) versus anorexigenic neural peptide signaling in the hypothalamus.…”
Section: Discussionmentioning
confidence: 61%
“…We observed that adult male offspring from obese mothers had higher body weight and food intake than offspring from CON mothers, confirming that maternal obesity can increase the risk of obesity in offspring, at least in males. This sex-specific response has been observed in some, 22,23 but not all, 24,25 previous rodent model studies investigating the transgenerational impact of maternal obesity. Previous work in rodent models suggests this hyperphagic/ obesogenic response may be mediated, at least partially, by altered expression of central appetite reward systems including preferential enhancement of orexigenic (NPY/AgRP) versus anorexigenic neural peptide signaling in the hypothalamus.…”
Section: Discussionmentioning
confidence: 61%
“…We observed that adult male offspring from HC-CP mothers had higher body weights and food intakes than offspring from CON mothers, confirming that maternal obesity can increase the risk of obesity in offspring, at least in males. This sex-specific response has been observed in some [ 45 , 46 ], but not all [ 47 , 48 ], previous rodent model studies investigating the transgenerational impact of maternal obesity. Chang et al (2019) reported that male mouse offspring born to mothers fed a high-fat diet before conception had greater weight gain and subcutaneous adipose mass compared with their female counterparts when exposed to a postnatal high-fat diet challenge [ 49 ].…”
Section: Discussionmentioning
confidence: 72%
“…A Brazilian cohort study conducted in 2015 revealed that 47% of women were classified as overweight or obese before pregnancy [4]. In addition, obesity in children and adolescents (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years old) has increased significantly. In 1975, the global prevalence of obesity was 0.7% among girls and 0.9% among boys.…”
Section: Introductionmentioning
confidence: 99%
“…These outcomes include impaired glucose metabolism and liver function, hyperactivity, cardiovascular disease, and obesity [7][8][9][10][11][12][13][14]. Maternal obesity can affect weight gain in offspring through various mechanisms, including its impact on hyperphagic mechanisms [15,16].…”
Section: Introductionmentioning
confidence: 99%